The Mediating Role of Cognitive Flexibility in the Influence of Counter-Stereotypes on Creativity - Zuo, Bin; Wen, Fangfang; Wang, Miao; Wang, Yang (Frontiers in Psychology, 2019)
Abstract The aim of this study is to explore the relationship between counter-stereotypes and creativity, and further explore the mechanism underlying the impact of priming counter-stereotypic information on individual creativity. More importantly, here we have proposed cognitive and emotional dual processing pathways, which may mediate the influences of counter-stereotypes on creativity. Two experiments examined how counter-stereotypes impacted creativity through the dual processing pathways. A total of 152 university students were recruited to test their creativity performance. In Experiment 1, we replicated results of past studies. Participants were randomly allocated to different priming conditions (stereotype or counter-stereotype), in which descriptions of male governors and female nurses served as priming of stereotypes, whereas descriptions of male nurses and female governors served as priming of counter-stereotypes. Measurements of creativity were based on the poster paradigm. The poster paradigm required participants to design a poster for a college fellowship party. In Experiment 2, we recruited 104 participants to examine the mediating roles of emotions and cognitive flexibility. The procedure of Experiment 2 was similar to that of Experiment 1, except for the measurement of creativity, which was Chinese idiom riddle test. Participants who selected more creative answers were more creative, based on the criteria of our experimental design. Also, we included measurements of emotions (i.e., surprise and delight) and cognitive flexibility (using the Cognitive Flexibility Scale) after priming of stereotypes and counter-stereotypes in Experiment 2. We also verified the credibility of our counter-stereotype measurements. The results of Experiment 1—which replicated previous studies—demonstrated that priming of counter-stereotypes promoted creative performance compared with priming of stereotypes in the poster paradigm. However, our proposed dual processing pathways were not fully verified by Experiment 2. The results of this experiment showed that neither surprising nor delighted emotion mediated the influence of counter-stereotypes on creativity, whereas cognitive flexibility did. In conclusion, our current study reveals a mechanism of creative performance in terms of cognitive flexibility, and further inspires us to focus on the positive influence of counter-stereotypes on creativity.